A case control study to assess clinical and lipid profile in patients with xanthelasma palpebrarum in a tertiary care centre (Panacea Journal of Medical Sciences, 2025)
Background: Xanthelasma palpebrarum is used to describe xanthoma that occurs on the eyelids or inner canthi of the eyes. It is frequently associated with cardiovascular disease, diabetes, obesity etc. Various authors have found a positive relationship between xanthelasma palpebrarum and lipid profile.Aim and Objective: Xanthelasma palpebrarum is a common condition observed in dermatology OPD for the cosmetic problem posed by it. Most of these patients would not have undergone a lipid profile and there is a need to know whether lipid profile is mandatory for all the patients presenting with xanthelasma palpebrarum. Hence this study was undertakenMaterials and Methods: In this case-control study, 55 subjects diagnosed with xanthelasma palpebrarum and 55 healthy controls were chosen. All cases and controls underwent detailed clinical examination and fasting lipid profile study.Results: Total cholesterol levels were found increased in 36 cases (65.5%) in contrast to 20 controls (36%) with p=0.004(highly significant).Increase in LDL cholesterol levels were found in 31 cases (56.4%) as against 15 controls (27%) making it statistically significant( p= 0.001). Other cholesterol fractions were not found to have a significant relationship.Conclusion: At the end of this study it was observed that there is a significant elevation in total cholesterol and LDL cholesterol in xanthelasma patients as compared to controls, thereby making lipid profile study mandatory for all patients.